2017
DOI: 10.1166/jnn.2017.13066
|View full text |Cite
|
Sign up to set email alerts
|

Effluent Disinfection of Real Wastewater by Ag–TiO2 Nanoparticles Photocatalysis

Abstract: Currently pathogen microorganisms, presents in wastewater, are more resistant to conventional disinfection process, due to its constant change induced for the antibiotic for human diseases. One of the new options for the pathogen microorganisms is the heterogeneous photocatalysis, which has been used for remove microorganism, but never in real wastewater effluent. This paper shown the synthesis of Ag–TiO₂ nanoparticles, its physical characterization was carried out by TEM, SEM, S-BET, XPS and band gap measurem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 0 publications
1
7
0
Order By: Relevance
“…Treating real wastewater containing a mixture of organic compounds, suspended solids, nitrogen and phosphorous compounds, heavy metals, and microorganisms (Schaider et al 2014;Mankiewicz-Boczek et al 2017) by photocatalysis process in general and Ag/TiO 2 as photocatalyst, in particular, is one of the important subjects. Silver-doped TiO 2 photocatalysts are also shown their higher photocatalytic efficiency toward simulated and real wastewater (Badawy et al 2014;Chaker et al 2016;Tio et al 2017;Mehrvar 2018;Gomes et al 2019). Chaker et al (2016) have synthesized Ag-doped mesoporous TiO 2 photocatalyst using a simple chemical method developed for the disinfection of real wastewater from a sewage treatment plant in the North of France, spiked with various toxic compounds, namely toluene, carbamazepine, methylene chloride, cholesterol, caffeine … etc.…”
Section: Real Wastewatermentioning
confidence: 99%
See 1 more Smart Citation
“…Treating real wastewater containing a mixture of organic compounds, suspended solids, nitrogen and phosphorous compounds, heavy metals, and microorganisms (Schaider et al 2014;Mankiewicz-Boczek et al 2017) by photocatalysis process in general and Ag/TiO 2 as photocatalyst, in particular, is one of the important subjects. Silver-doped TiO 2 photocatalysts are also shown their higher photocatalytic efficiency toward simulated and real wastewater (Badawy et al 2014;Chaker et al 2016;Tio et al 2017;Mehrvar 2018;Gomes et al 2019). Chaker et al (2016) have synthesized Ag-doped mesoporous TiO 2 photocatalyst using a simple chemical method developed for the disinfection of real wastewater from a sewage treatment plant in the North of France, spiked with various toxic compounds, namely toluene, carbamazepine, methylene chloride, cholesterol, caffeine … etc.…”
Section: Real Wastewatermentioning
confidence: 99%
“…At optimal conditions, Ag doped mesoporous TiO 2 was able to totally pollutants mineralization after 3 and 4 h under UV and visible light irradiations, respectively. Similarly, Rodríguez-Méndez et al (Tio et al 2017) have prepared Ag/TiO 2 nanoparticles with different concentrations of silver via a sol-gel method for disinfection of real wastewater from an activated sludge biological treatment and containing pathogenic bacteria, known by their strong resistance. It was found that the increase of silver amount in the photocatalyst has no effect in the disinfection tests; small amount of silver shows similar results to those obtained by adding a higher silver concentration.…”
Section: Real Wastewatermentioning
confidence: 99%
“…Among the qualities of the material, low toxicity, chemical stability, and high availability stand out as advantages over other semiconductors. Also, due to these characteristics, TiO 2 is one of the most employed photocatalyst [36][37][38].…”
Section: Theory Behind the Physico-chemical Characteristics In Sio 2 mentioning
confidence: 99%
“…The degradation processes of the catalysts mentioned above are mainly carried out in wastewater treatments to remove recalcitrant and persistent pollutants such as dyes and pharmaceutical compounds, and the catalysts even work as disinfection agents [ 23 , 24 , 25 , 26 ]. The remaining effluents are used for watering some crop fields without any proper legislation [ 27 , 28 ], and no toxicology studies are well substantiated yet, because the remained NPs in the effluents are considered not dangerous in low concentrations. Nevertheless, a new research area is emerging to contribute some broader knowledge to differentiate the pro and cons of using these materials in agriculture systems [ 29 ].…”
Section: Nanomaterials Classificationmentioning
confidence: 99%
“…Their applications include their use in solar cells, structural materials, electronics, and semiconductors, which is mainly due to their interesting properties such as semiconductor behavior, thermal conductivity, high structural properties, and light absorption properties [ 30 ]. Carbon nanotubes are also classified depending on their number of walls, which can be single-wall, double-wall, or multi-wall; the number of walls will modify their structural and conductive characteristics [ 27 , 34 ].…”
Section: Nanomaterials Classificationmentioning
confidence: 99%